2011
DOI: 10.1108/09654281111144256
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships among nutrition knowledge, attitudes, behaviors and body satisfaction

Abstract: PurposeLittle is known about interrelationships among nutrition knowledge, attitude, dietary intake, and body satisfaction, which are important variables that play a role in nutrition education interventions. This paper aims to focus on these interrelationships.Design/methodology/approachStudents (n=279; 20.12±1.75SD years) enrolled at a large northeastern US university took an online survey. The survey contained a nutrition knowledge scale, attitude scale, food frequency scales, body areas satisfaction subsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
1
15
0
2
Order By: Relevance
“…On-campus students rely on the Wesley College cafeteria which has a buffet-style arrangement. Hence, the greater than normal BMI for students living on-campus affirms prior associations (Wansink and Payne, 2008; Dissen et al, 2011) exhibited by buffet patrons.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On-campus students rely on the Wesley College cafeteria which has a buffet-style arrangement. Hence, the greater than normal BMI for students living on-campus affirms prior associations (Wansink and Payne, 2008; Dissen et al, 2011) exhibited by buffet patrons.…”
Section: Discussionsupporting
confidence: 57%
“…National concern about obesity on campus (Sparling, 2007) has identified probable causes to include campus culture (Cash and Green, 1986; Betz et al, 1994; Brener and Gowda, 2001; Costin, 2013), diet and exercise (Haberman and Luffey, 1998), gender (Hoerr et al, 2002), college standing (Driskel, Kim, and Goebel, 2005), demographics (James and Bonds, 2006; Sira and Pawlak, 2010; Wang and Beydoun, 2007), stress (Torres and Nowson, 2007), living arrangements (Brunt and Rhee, 2008), and student nutritional knowledge and attitudes (Wansink and Payne, 2008; Dissen et al, 2011). Although behavior, environment, and family history (Ellis and Haman, 2004) do play a role in obesity, studies consistently show that consuming too many calories and not getting enough physical activity is still the main leading cause of obesity in the US population (US Dept.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Kostanjevec et al [56] observed a significant improvement in nutrition knowledge, however, only participants scoring low at baseline made the most improvement while those scoring best at baseline did not improve significantly. Dissen et al [9] also reported that nutrition interventions should aim at increasing nutrition knowledge as higher nutrition knowledge levels may lead to more positive changes and promote healthier dietary habits. There are contradictory results where knowledge scores did not increase significantly from pre-test to post-test [57] which may be due to differences in the exposure to nutrition information, family environment, and food availability and accessibility [58].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary behaviors are affected by many factors including nutrition knowledge. For example, individuals who have been taught about the health benefits of eating larger quantities of fruits and vegetables are more likely to consume these foods than those who were not taught [9]. Attitudes toward nutrition and health also affect dietary behavior.…”
Section: Introductionmentioning
confidence: 99%
“…There is a corpus of studies indicating that knowledge about nutrition issues is associated with behavioral intention and performance (e.g., [51][52][53]). Other studies, however, point to the exact opposite (e.g., [54,55]). Reasons for this inconsistency can be found in the subject matter and its complexity, as well as in the process of human decision-making [56].…”
Section: Theoretical Backgroundmentioning
confidence: 94%